Isolation of Ethyl p-Methoxycinnamate from Azadirachta indica Root Bark as Hong Kong Caterpillar (Tenebrio molitor) Antifeedant - Rosnani Nasution; Cut Nyak Candein; Nurdin Saidi; Muhammad Bahi; Marianne Marianne (Universitas Gadjah Mada, 2021)
This study aims to identify the antifeedant activity of Azadirachta indica A. Juss root bark against Hong Kong caterpillar (Tenebrio molitor). A. indica A. root was macerated in n-hexane, ethyl acetate, and methanol. The investigation of antifeedant activity was conducted by using the no choice leaf disk method. The antifeedant activity (%AI) tests showed that the extracts of n-hexane, ethyl acetate, and methanol with each concentration of 0.5% were 6.71, 71.78, and 40.14%, respectively. The ethyl acetate extract demonstrated the most active antifeedant activity. Ethyl acetate extract was fractionated to obtain five subfractions (A-E). Each subfraction with each concentration of 0.5% showed the %AI of 70.55, 85.29; 67.40, 82.70 and 82.22%, respectively. Furthermore, GC-MS results demonstrated that ethyl acetate extract contained 19 compounds. The main compounds are methyl hexadecanoate and methyl 8-octadecenoate. Further purification of fraction A, which has the highest amount, was then carried out. The obtained isolate, i.e., A32, was determined as ethyl p-methoxycinnamate confirmed by 13C- and 1H-NMR, FTIR, and MS spectra. The presence of ethyl p-methoxycinnamate makes A. indica A. root is potential as T. molitor antifeedant. The implication of these findings is to reference herbal antifeedants and reduce the use of synthetic pesticides.